A high temperature resistant inorganic glue, preparation method, application and method for limiting CVD diamond seed drift

By using high-temperature resistant inorganic adhesives to enhance the adhesion between CVD diamond seeds and molybdenum sheets, the problem of seed drift is solved, and stable seed growth and convenient sample processing is achieved.

CN116144271BActive Publication Date: 2025-04-15SHANGHAI JINGSHI INNOVATIVE MATERIALS TECH CO LTD

Patent Information

Application Number
CN202310144889.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-04-15
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

In the early stage of CVD diamond seed growth, due to the inadequate bond between the seed and the molybdenum sheet, the seeds tend to drift and fly out of the molybdenum sheet area during the heating process, resulting in interruption of growth.

Method used

Using a high-temperature resistant inorganic adhesive, including aluminum silicate, aluminum phosphate, copper-copper-titanium-diamond composite or copper-titanium-diamond composite, phosphoric acid and dispersant, the adhesion between the seed and molybdenum sheet is enhanced by coating the bottom of the CVD diamond seed and curing.

Benefits of technology

The drift of CVD diamond seeds is effectively limited, ensuring that the seeds can be stably bonded to the molybdenum sheet, avoiding growth interruption, and the seeds can be easily removed from the molybdenum sheet when needed.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a high temperature resistant inorganic glue, a preparation method, an application and a method for limiting the drift of CVD seed crystals. The high temperature resistant inorganic glue comprises: 100 to 400 parts by weight of aluminum silicate; 50 to 200 parts by weight of aluminum phosphate; 50 to 400 parts by weight of copper oxide-copper-titanium-diamond composite material or copper oxide-titanium-diamond composite material; 50 to 200 parts by weight of phosphoric acid; and 100 to 400 parts by weight of a dispersant. The method for limiting the drift of CVD diamond seed crystals is to apply a high temperature resistant inorganic glue on the bottom of the CVD diamond seed crystal before the chemical vapor deposition growth of the CVD diamond seed crystal, press it flat on a molybdenum sheet and solidify it. The high temperature resistant inorganic glue of the present invention can withstand temperatures above 1200°C and is easy to glue and remove; the CVD diamond seed crystal is bonded to the molybdenum sheet by the high temperature resistant inorganic glue, and the seed crystal drift is limited during chemical vapor deposition growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic glue and diamond, and in particular to a high temperature resistant inorganic glue, a preparation method, an application and a method for limiting CVD seed drift. Background Art

[0002] In the early stage of CVD diamond seed growth, due to the thinness and lightness of the seed, the friction between the bottom of the seed and the deposition platform such as the molybdenum sheet is insufficient. During the heating process, the gas adsorbed on the surface of the molybdenum sheet desorbs, causing the diamond and the molybdenum sheet to form an "air cushion", which can easily cause the sample to move, float around, or even drift out of the molybdenum sheet area and fail to grow. Common treatment methods include grooving the molybdenum sheet to limit the range of seed drift and roughening the surface of the molybdenum sheet, but the seed may still fly out of the groove, resulting in growth interruption. Summary of the invention

[0003] The purpose of the present invention is to provide a high temperature resistant inorganic glue, a preparation method, an application and a method for limiting CVD seed drift, so as to solve the problem of gold CVD diamond seed drift in the prior art.

[0004] In order to achieve the above-mentioned object and other related objects, the first aspect of the present invention provides a high temperature resistant inorganic adhesive, comprising the following components:

[0005] 100-400 parts by weight of aluminum silicate, such as 100-200 parts by weight, 200-300 parts by weight or 300-400 parts by weight;

[0006] 50-200 parts by weight of aluminum phosphate, such as 50-100 parts by weight, 100-150 parts by weight or 150-200 parts by weight;

[0007] 50 to 400 parts by weight of a copper oxide-copper-titanium-diamond composite material or a copper oxide-titanium-diamond composite material, such as 50 to 150 parts by weight, 150 to 200 parts by weight or 200 to 400 parts by weight;

[0008] Phosphoric acid 50-200 parts by weight, such as 50-100 parts by weight, 100-150 parts by weight or 150-200 parts by weight;

[0009] The dispersant is 100-400 parts by weight, such as 100-200 parts by weight, 200-300 parts by weight or 300-400 parts by weight.

[0010] Preferably, based on the total mass of the copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material, the mass percentage of each component is as follows:

[0011] Diamond 73-98.9%, such as 73-81%, 81-90% or 90-98.9%;

[0012] Titanium 0.1-2%, such as 0.1-1%, 1-1.5% or 1.5-2%;

[0013] Copper 0-20%, such as 0-4.5%, 4.5-15% or 15-20%;

[0014] Copper oxide 1-5%, such as 1-3%, 3-4% or 4-5%;

[0015] and / or, the copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material has a particle size of 5 to 40 μm, such as 5 to 10 μm, 10 to 20 μm, 20 to 30 μm or 30 to 40 μm;

[0016] And / or, the copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material is obtained by a preparation method comprising the following steps:

[0017] 1) heating, heat preservation, cooling and screening diamond and titanium powder under vacuum conditions to obtain diamond with titanium coating on the surface;

[0018] 2) electroplating copper on the titanium-plated diamond obtained in step 1) to obtain a copper-titanium-diamond composite material;

[0019] 3) partially or completely oxidizing and screening the surface copper of the copper-titanium-diamond composite material obtained in step 2) under oxygen conditions;

[0020] And / or, the dispersant is selected from at least one of water and ethanol.

[0021] More preferably, in step 1), the diamond particle size is 5 to 30 μm, such as 5 to 10 μm, 10 to 20 μm or 20 to 30 μm;

[0022] And / or, in step 1), the particle size of the titanium powder is 100-400 mesh, such as 100-110 mesh, 110-120 mesh, 120-130 mesh, 130-190 mesh or 190-400 mesh;

[0023] And / or, in step 1), the heating temperature is 800-1200° C., such as 800-900° C., 900-1000° C. or 1000-1200° C.;

[0024] And / or, in step 1), the insulation time is 2 to 12 hours, such as 2 to 6 hours, 6 to 8 hours or 8 to 12 hours;

[0025] And / or, in step 1), the cooling rate is 2-20°C / min, such as 2-10°C / min, 10-15°C / min or 15-20°C / min;

[0026] And / or, in step 1), the mesh size of the sieving is 5-40 μm, such as 5-10 μm, 10-20 μm, 20-30 μm or 30-40 μm;

[0027] And / or, in step 2), the titanium-plated diamond obtained in step 1) is placed in an electroplating device for copper electroplating;

[0028] And / or, in step 2), the solution used for copper electroplating is a copper sulfate solution;

[0029] And / or, in step 2), the copper electroplating time is 0.5 to 6 hours, such as 0.5 to 3 hours, 3 to 5 hours or 5 to 6 hours;

[0030] And / or, in step 3), the oxidation temperature is 500-800°C, such as 500-600°C, 600-700°C or 700-800°C;

[0031] And / or, in step 3), heating to an oxidation temperature using a fluidized bed;

[0032] And / or, in step 3), the mesh size of the sieving is 5-40 μm, such as 5-10 μm, 10-20 μm, 20-30 μm or 30-40 μm.

[0033] The second aspect of the present invention provides a method for preparing the above-mentioned high temperature resistant inorganic glue, wherein the components are mixed and ground to obtain the high temperature resistant inorganic glue, which can be ground to a particle size of less than 600 meshes.

[0034] The third aspect of the present invention provides the use of the above-mentioned high temperature resistant inorganic glue in limiting the drift of CVD diamond seed crystals.

[0035] Preferably, before the CVD diamond seed crystal is grown by chemical vapor deposition, the high temperature resistant inorganic glue is coated on the bottom of the CVD diamond seed crystal, flatly pressed on the molybdenum sheet and cured.

[0036] More preferably, it also includes at least one of the following technical features:

[0037] a1) the curing temperature is 100-140°C, such as 100-120°C, 120-130°C or 130-140°C;

[0038] a2) The curing time is 1 to 3 hours, such as 1 to 2 hours, 2 to 2.5 hours or 2.5 to 3 hours;

[0039] a3) After solidification, the first heating and heat preservation, the second heating and heat preservation and the third heating and heat preservation are carried out, and then the temperature is lowered to clean the surface of the CVD diamond seed crystal.

[0040] Even more preferably, feature a3) further includes at least one of the following technical features:

[0041] a31) The temperature after heating in the first heating and holding process is 450-550°C, such as 450-500°C, 500-525°C or 525-550°C;

[0042] a32) The holding time in the first heating and holding is 0.5 to 1.5 h, such as 0.5 to 1 h, 1 to 1.1 h or 1.1 to 1.5 h;

[0043] a33) The temperature after heating in the second heating and insulation is 950-1050°C, such as 950-980°C, 980-1000°C or 1000-1050°C;

[0044] a34) The holding time in the second heating and holding period is 0.5 to 1.5 h, such as 0.5 to 1 h or 1 to 1.5 h;

[0045] a35) The temperature after heating in the third heating and holding process is 1150-1250°C, such as 1150-1180°C, 1180-1200°C or 1200-1250°C;

[0046] a36) The holding time in the third heating and holding is 0.5 to 1.5 h, such as 0.5 to 0.8 h, 0.8 to 1 h or 1 to 1.5 h;

[0047] a37) After the third heating and holding, the temperature is lowered again to clean the surface of the CVD diamond seed crystal.

[0048] A fourth aspect of the present invention provides a method for limiting the drift of CVD diamond seeds. Before the CVD diamond seeds are grown by chemical vapor deposition, the high temperature resistant inorganic glue is coated on the bottom of the CVD diamond seeds, pressed flat on a molybdenum sheet and cured.

[0049] Preferably, it also includes at least one of the following technical features:

[0050] b1) the curing temperature is 100-140°C, such as 100-120°C, 120-130°C or 130-140°C;

[0051] b2) The curing time is 1 to 3 hours, such as 1 to 2 hours, 2 to 2.5 hours or 2.5 to 3 hours;

[0052] b3) After solidification, the first heating and heat preservation, the second heating and heat preservation and the third heating and heat preservation are performed, and then the temperature is lowered to clean the surface of the CVD diamond seed crystal.

[0053] More preferably, feature b3) further includes at least one of the following technical features:

[0054] b31) The temperature after heating in the first heating and holding process is 450-550°C, such as 450-500°C, 500-525°C or 525-550°C;

[0055] b32) The holding time of the first heating and holding is 0.5 to 1.5 h, such as 0.5 to 1 h, 1 to 1.1 h or 1.1 to 1.5 h;

[0056] b33) the temperature after heating in the second heating and insulation is 950-1050°C, such as 950-980°C, 980-1000°C or 1000-1050°C;

[0057] b34) The holding time in the second heating and holding period is 0.5 to 1.5 h, such as 0.5 to 1 h or 1 to 1.5 h;

[0058] b35) The temperature after heating in the third heating and holding is 1150-1250°C, such as 1150-1180°C, 1180-1200°C or 1200-1250°C;

[0059] b36) The holding time in the third heating and holding is 0.5 to 1.5 h, such as 0.5 to 0.8 h, 0.8 to 1 h or 1 to 1.5 h;

[0060] b37) After the third heating and holding, the temperature is lowered again to clean the surface of the CVD diamond seed crystal.

[0061] The above technical solution has at least one of the following beneficial effects:

[0062] 1) The high temperature resistant inorganic adhesive of the present invention can withstand temperatures above 1200°C;

[0063] 2) After the high temperature resistant inorganic adhesive of the present invention is used to bond the CVD diamond seed crystal to the molybdenum sheet, the CVD diamond seed crystal can be easily removed from the molybdenum sheet by soaking it in water for a period of time, which is convenient and quick;

[0064] 3) The present invention bonds the CVD diamond seed to the molybdenum sheet by means of a high temperature resistant inorganic adhesive, thereby limiting the drift of the CVD seed during chemical vapor deposition growth. The process is convenient and quick, and the CVD diamond seed can be bonded to the molybdenum sheet at any time and can be easily removed from the molybdenum sheet (only needs to be soaked in water for a period of time), thus saving costs and not requiring grooving of the deposition platform. DETAILED DESCRIPTION

[0065] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0066] Example 1

[0067] High temperature resistant inorganic glue includes the following components:

[0068] 100 parts by weight of aluminum silicate;

[0069] 50 parts by weight of aluminum phosphate;

[0070] 150 parts by weight of copper oxide-copper-titanium-diamond composite material;

[0071] Phosphoric acid 100 parts by weight;

[0072] Water: 100 parts by weight.

[0073] Based on the total mass of the copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material, the mass percentage of each component is as follows:

[0074] Diamond 73%;

[0075] Titanium 2%;

[0076] Copper 20%;

[0077] Copper oxide 5%;

[0078] The copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material has a particle size of 5 to 40 μm; the copper oxide-copper-titanium-diamond composite material is obtained by a preparation method comprising the following steps:

[0079] 1) Heating, heat preservation, cooling and screening diamond and titanium powder under vacuum conditions to obtain diamond with titanium coating on the surface; wherein the particle size of the diamond is 5-10 μm; the particle size of the titanium powder is 100-110 mesh; the heating temperature is 800° C.; the heat preservation time is 12 h; the cooling rate is 10° C. / min; the mesh size of the screening is 40 μm;

[0080] 2) electroplating copper on the titanium-plated diamond obtained in step 1) to obtain a copper-titanium-diamond composite material; wherein the titanium-plated diamond obtained in step 1) is placed in an electroplating device for copper electroplating; the solution used for copper electroplating is a copper sulfate solution; and the copper electroplating time is 6 hours;

[0081] 3) Partially or completely oxidizing the surface copper of the copper-titanium-diamond composite material obtained in step 2) under oxygen conditions and screening; wherein the oxidation temperature is 700° C.; a fluidized bed is used to heat to the oxidation temperature; and the screening mesh size is 40 μm.

[0082] The preparation method of high temperature resistant inorganic glue is as follows: the above components are mixed and ground evenly to obtain the same.

[0083] The method for limiting the drift of CVD diamond seed is as follows: before the CVD diamond seed is chemically vapor deposited and grown, the high temperature resistant inorganic glue is coated on the bottom of the CVD diamond seed, and the CVD diamond seed is pressed flat on a molybdenum sheet. The fingers can press and move the CVD diamond seed forward, backward, left and right, squeeze out the excess high temperature resistant inorganic glue from the bottom of the CVD diamond seed, wipe off the glue around the CVD diamond seed, place it in a vacuum furnace, heat to 120°C and keep it for 2.5h (curing), heat to 500°C and keep it for 0.5h (first heating and keeping), heat to 1000°C and keep it for 1h (second heating and keeping), heat to 1200°C and keep it for 0.5h (third heating and keeping). Cool down to room temperature at a rate of 10°C / min, take it out, and wipe off dust and particles on the surface of the sample. Then it was placed in a CVD deposition equipment, and hydrogen and oxygen were first introduced for etching, with a hydrogen flow rate of 600sccm, an oxygen flow rate of 0.04sccm, an etching temperature of 800°C, and an etching time of 2h; hydrogen and methane were introduced for growth, with a chemical vapor deposition power of 6000W, a chemical vapor deposition pressure of 35kpa, a chemical vapor deposition temperature of 1200°C, a hydrogen flow rate of 1000sccm, and a methane flow rate of 100sccm. No CVD diamond seed drift occurred during the growth process.

[0084] The bonded CVD diamond seed crystal and molybdenum sheet that were cooled to room temperature were inverted, and no CVD diamond seed crystal fell off.

[0085] The bonded CVD diamond seed crystal and molybdenum sheet cooled to room temperature were immersed in water for 8 hours, and the CVD diamond seed crystal was separated from the molybdenum sheet.

[0086] Example 2

[0087] High temperature resistant inorganic glue includes the following components:

[0088] 300 parts by weight of aluminum silicate;

[0089] 200 parts by weight of aluminum phosphate;

[0090] 200 parts by weight of copper oxide-copper-titanium-diamond composite material;

[0091] Phosphoric acid 50 parts by weight;

[0092] 300 parts by weight of ethanol.

[0093] Based on the total mass of the copper oxide-titanium-diamond composite material, the mass percentage of each component is as follows:

[0094] Diamond 98.9%;

[0095] Titanium 0.1%;

[0096] Copper oxide 1%;

[0097] The particle size of the copper oxide-titanium-diamond composite material is 5 to 40 μm; the copper oxide-copper-titanium-diamond composite material is obtained by a preparation method comprising the following steps:

[0098] 1) Heating, heat preservation, cooling and screening diamond and titanium powder under vacuum conditions to obtain diamond with titanium coating on the surface; wherein the particle size of the diamond is 10-30 μm; the particle size of the titanium powder is 120-190 mesh; the heating temperature is 1200° C.; the heat preservation time is 8 hours; the cooling rate is 20° C. / min; the mesh size of the screening is 30 μm;

[0099] 2) electroplating copper on the titanium-plated diamond obtained in step 1) to obtain a copper-titanium-diamond composite material; wherein the titanium-plated diamond obtained in step 1) is placed in an electroplating device for copper electroplating; the solution used for copper electroplating is a copper sulfate solution; and the copper electroplating time is 3 hours;

[0100] 3) The copper-titanium-diamond composite material obtained in step 2) is subjected to complete oxidation of the surface copper and screening under oxygen conditions; wherein the oxidation temperature is 800° C.; a fluidized bed is used to heat to the oxidation temperature; and the screening mesh size is 30 μm.

[0101] The preparation method of high temperature resistant inorganic glue is as follows: the above components are mixed and ground evenly to obtain the same.

[0102] The method for limiting the drift of CVD diamond seed is as follows: before the chemical vapor deposition growth of CVD diamond seed, the bottom of CVD diamond seed is coated with the high temperature resistant inorganic glue, and flatly pressed on a molybdenum sheet, the CVD diamond seed can be pressed and moved back and forth and left and right by fingers, and the excess high temperature resistant inorganic glue is squeezed out of the bottom of the CVD diamond seed, and the glue around the CVD diamond seed is wiped off, and the CVD diamond seed is placed in a vacuum furnace, heated to 140°C for 1 hour (curing), heated to 450°C for 1 hour (first heating and insulation), heated to 950°C for 1.5 hours (second heating and insulation), and heated to 1250°C for 0.8 hours (third heating and insulation). The sample is cooled to room temperature at a rate of 10°C / min, taken out, and dust and particles on the surface of the sample are wiped off. Then it was placed in a CVD deposition equipment, and hydrogen and oxygen were first introduced for etching, with a hydrogen flow rate of 600sccm, an oxygen flow rate of 0.04sccm, an etching temperature of 800°C, and an etching time of 2h; hydrogen and methane were introduced for growth, with a chemical vapor deposition power of 6000W, a chemical vapor deposition pressure of 35kpa, a chemical vapor deposition temperature of 1200°C, a hydrogen flow rate of 1000sccm, and a methane flow rate of 100sccm. No CVD diamond seed drift occurred during the growth process.

[0103] The bonded CVD diamond seed crystal and molybdenum sheet that were cooled to room temperature were inverted, and no CVD diamond seed crystal fell off.

[0104] The bonded CVD diamond seed crystal and molybdenum sheet cooled to room temperature were immersed in water for 8 hours, and the CVD diamond seed crystal was separated from the molybdenum sheet.

[0105] Example 3

[0106] High temperature resistant inorganic glue includes the following components:

[0107] 400 parts by weight of aluminum silicate;

[0108] 150 parts by weight of aluminum phosphate;

[0109] 400 parts by weight of copper oxide-copper-titanium-diamond composite material;

[0110] Phosphoric acid 150 parts by weight;

[0111] 400 parts by weight of water.

[0112] Based on the total mass of the copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material, the mass percentage of each component is as follows:

[0113] Diamond 81%;

[0114] Titanium 1%;

[0115] Copper 15%;

[0116] Copper oxide 3%;

[0117] The copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material has a particle size of 5 to 20 μm; the copper oxide-copper-titanium-diamond composite material is obtained by a preparation method comprising the following steps:

[0118] 1) Heating, heat preservation, cooling and screening diamond and titanium powder under vacuum conditions to obtain diamond with titanium coating on the surface; wherein the particle size of the diamond is 5-20 μm; the particle size of the titanium powder is 100-130 mesh; the heating temperature is 1000° C.; the heat preservation time is 2 h; the cooling rate is 2° C. / min; the sieving mesh size is 20 μm;

[0119] 2) electroplating copper on the titanium-plated diamond obtained in step 1) to obtain a copper-titanium-diamond composite material; wherein the titanium-plated diamond obtained in step 1) is placed in an electroplating device for copper electroplating; the solution used for copper electroplating is a copper sulfate solution; and the copper electroplating time is 0.5 h;

[0120] 3) Partially or completely oxidizing the surface copper of the copper-titanium-diamond composite material obtained in step 2) under oxygen conditions and screening; wherein the oxidation temperature is 500° C.; a fluidized bed is used to heat to the oxidation temperature; and the screening mesh size is 20 μm.

[0121] The preparation method of high temperature resistant inorganic glue is as follows: the above components are mixed and ground evenly to obtain the same.

[0122] The method for limiting the drift of CVD diamond seed is as follows: before the CVD diamond seed is chemically vapor deposited and grown, the bottom of the CVD diamond seed is coated with the high temperature resistant inorganic glue, and the CVD diamond seed is pressed flat on a molybdenum sheet. The fingers can press and move the CVD diamond seed forward, backward, left and right, squeeze the excess high temperature resistant inorganic glue out of the bottom of the CVD diamond seed, wipe off the glue around the CVD diamond seed, place it in a vacuum furnace, heat to 100°C for 3 hours (curing), heat to 550°C for 1.5 hours (first heating and heat preservation), heat to 1050°C for 0.5 hours (second heating and heat preservation), heat to 1150°C for 1.5 hours (third heating and heat preservation), cool to room temperature at a rate of 10°C / min, take it out, and wipe off dust and particles on the surface of the sample. Then it was placed in a CVD deposition equipment, and hydrogen and oxygen were first introduced for etching, with a hydrogen flow rate of 600sccm, an oxygen flow rate of 0.04sccm, an etching temperature of 800°C, and an etching time of 2h; hydrogen and methane were introduced for growth, with a chemical vapor deposition power of 6000W, a chemical vapor deposition pressure of 35kpa, a chemical vapor deposition temperature of 1200°C, a hydrogen flow rate of 1000sccm, and a methane flow rate of 100sccm. No CVD diamond seed drift occurred during the growth process.

[0123] The bonded CVD diamond seed crystal and molybdenum sheet that were cooled to room temperature were inverted, and no CVD diamond seed crystal fell off.

[0124] The bonded CVD diamond seed crystal and molybdenum sheet cooled to room temperature were immersed in water for 8 hours, and the CVD diamond seed crystal was separated from the molybdenum sheet.

[0125] Example 4

[0126] High temperature resistant inorganic glue includes the following components:

[0127] 200 parts by weight of aluminum silicate;

[0128] 100 parts by weight of aluminum phosphate;

[0129] 50 parts by weight of copper oxide-titanium-diamond composite material;

[0130] Phosphoric acid 200 parts by weight;

[0131] 200 parts by weight of water.

[0132] Based on the total mass of the copper oxide-titanium-diamond composite material, the mass percentage of each component is as follows:

[0133] Diamond 90%;

[0134] Titanium 1.5%;

[0135] Copper 4.5% Copper oxide 4%;

[0136] The particle size of the copper oxide-titanium-diamond composite material is 5 to 10 μm; the copper oxide-titanium-diamond composite material is obtained by a preparation method comprising the following steps:

[0137] 1) Diamond and titanium powder are heated, kept warm, cooled and screened under vacuum conditions to obtain diamond with titanium coating on the surface; wherein the particle size of the diamond is 5-10 μm; the particle size of the titanium powder is 100-110 mesh; the heating temperature is 900° C.; the holding time is 6 hours; the cooling rate is 15° C. / min; the mesh size of the screening is 10 μm;

[0138] 2) electroplating copper on the titanium-plated diamond obtained in step 1) to obtain a copper-titanium-diamond composite material; wherein the titanium-plated diamond obtained in step 1) is placed in an electroplating device for copper electroplating; the solution used for copper electroplating is a copper sulfate solution; and the copper electroplating time is 5 hours;

[0139] 3) Partially or completely oxidizing the surface copper of the copper-titanium-diamond composite material obtained in step 2) under oxygen conditions and screening; wherein the oxidation temperature is 600° C.; a fluidized bed is used to heat to the oxidation temperature; and the screening mesh size is 10 μm.

[0140] The preparation method of high temperature resistant inorganic glue is as follows: the above components are mixed and ground evenly to obtain the same.

[0141] The method for limiting the drift of CVD diamond seed is as follows: before the chemical vapor deposition growth of CVD diamond seed, the bottom of CVD diamond seed is coated with the high temperature resistant inorganic glue, and flatly pressed on a molybdenum sheet, the CVD diamond seed can be pressed and moved back and forth and left and right by fingers, and the excess high temperature resistant inorganic glue is squeezed out of the bottom of the CVD diamond seed, and the glue around the CVD diamond seed is wiped off, and the CVD diamond seed is placed in a vacuum furnace, heated to 130°C for 2 hours (curing), heated to 525°C for 1.1 hours (first heating and heat preservation), heated to 980°C for 1 hour (second heating and heat preservation), and heated to 1180°C for 1 hour (third heating and heat preservation). The sample is cooled to room temperature at a rate of 10°C / min, taken out, and dust and particles on the surface of the sample are wiped off. Then it was placed in a CVD deposition equipment, and hydrogen and oxygen were first introduced for etching, with a hydrogen flow rate of 600sccm, an oxygen flow rate of 0.04sccm, an etching temperature of 800°C, and an etching time of 2h; hydrogen and methane were introduced for growth, with a chemical vapor deposition power of 6000W, a chemical vapor deposition pressure of 35kpa, a chemical vapor deposition temperature of 1200°C, a hydrogen flow rate of 1000sccm, and a methane flow rate of 100sccm. No CVD diamond seed drift occurred during the growth process.

[0142] The bonded CVD diamond seed crystal and molybdenum sheet that were cooled to room temperature were inverted, and no CVD diamond seed crystal fell off.

[0143] The bonded CVD diamond seed crystal and molybdenum sheet cooled to room temperature were immersed in water for 8 hours, and the CVD diamond seed crystal was separated from the molybdenum sheet.

[0144] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0145] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A high temperature resistant inorganic adhesive, characterized in that: The components include: 100-400 parts by weight of aluminum silicate; 50-200 parts by weight of aluminum phosphate; 50-400 parts by weight of copper oxide-copper-titanium-diamond composite material or copper oxide-titanium-diamond composite material; Phosphoric acid 50-200 parts by weight; Dispersant 100-400 parts by weight; Wherein, based on the total mass of the copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material, the mass percentage of each component is as follows: Diamond 73~98.9%; Titanium 0.1~2%; Copper 0~20%; Copper oxide 1~5%; The copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material is obtained by a preparation method comprising the following steps: 1) Diamond and titanium powder are heated, kept warm, cooled and screened under vacuum conditions to obtain diamond with titanium coating on the surface; 2) electroplating copper on the titanium-plated diamond obtained in step 1) to obtain a copper-titanium-diamond composite material; 3) Partially or completely oxidize the surface copper of the copper-titanium-diamond composite material obtained in step 2) under oxygen conditions and screen it.

2. The high temperature resistant inorganic adhesive according to claim 1, characterized in that: The particle size of the copper oxide-copper-titanium-diamond composite material or the copper oxide-titanium-diamond composite material is 5 to 40 μm; And / or, the dispersant is selected from at least one of water and ethanol.

3. The high temperature resistant inorganic adhesive according to claim 2, characterized in that: In step 1), the diamond particle size is 5-30 μm; And / or, in step 1), the particle size of the titanium powder is 100-400 mesh; And / or, in step 1), the heating temperature is 800-1200°C; And / or, in step 1), the insulation time is 2 to 12 hours; And / or, in step 1), the cooling rate is 2-20°C / min; And / or, in step 1), the mesh size of the sieving is 5-40 μm; And / or, in step 2), the titanium-plated diamond obtained in step 1) is placed in an electroplating device for copper electroplating; And / or, in step 2), the solution used for copper electroplating is a copper sulfate solution; And / or, in step 2), the copper electroplating time is 0.5 to 6 hours; And / or, in step 3), the oxidation temperature is 500-800°C; And / or, in step 3), a fluidized bed is used for heating to an oxidation temperature.

4. The method for preparing a high temperature resistant inorganic adhesive according to any one of claims 1 to 3, characterized in that: The components are mixed and ground to obtain the high temperature resistant inorganic glue.

5. Use of the high temperature resistant inorganic glue as claimed in any one of claims 1 to 3 in limiting the drift of CVD diamond seed crystals.

6. The use according to claim 5, characterized in that Before the CVD diamond seed crystal is grown by chemical vapor deposition, the high temperature resistant inorganic glue is coated on the bottom of the CVD diamond seed crystal, flatly pressed on the molybdenum sheet and cured.

7. The use according to claim 6, characterized in that Also includes at least one of the following technical features: a1) Curing temperature is 100~140℃; a2) Curing time is 1~3h; a3) After solidification, the first heating and heat preservation, the second heating and heat preservation and the third heating and heat preservation are carried out.

8. The use according to claim 7, characterized in that Feature a3) also includes at least one of the following technical features: a31) The temperature after heating in the first heating and insulation is 450~550℃; a32) The first heating and insulation time is 0.5~1.5h; a33) The temperature after the second heating and insulation is 950~1050℃; a34) The holding time of the second heating and holding period is 0.5~1.5 h; a35) The temperature after the third heating and insulation is 1150~1250℃; a36) The insulation time for the third heating and insulation is 0.5~1.5h; a37) After the third heating and holding, cool down again to clean the surface of the CVD diamond seed crystal.

9. A method for limiting CVD diamond seed drift, characterized in that: Before the CVD diamond seed crystal is grown by chemical vapor deposition, the high temperature resistant inorganic glue according to any one of claims 1 to 3 is coated on the bottom of the CVD diamond seed crystal, flatly pressed on a molybdenum sheet and cured.

10. The method for limiting CVD diamond seed drift according to claim 9, characterized in that: Also includes at least one of the following technical features: b1) Curing temperature is 100~140℃; b2) Curing time is 1~3h; b3) After solidification, the first heating and heat preservation, the second heating and heat preservation and the third heating and heat preservation are carried out.

11. The method for limiting CVD diamond seed drift according to claim 10, characterized in that: Also includes at least one of the following technical features: b31) The temperature after heating in the first heating and insulation is 450~550℃; b32) The holding time for the first heating and holding is 0.5~1.5h; b33) The temperature after the second heating and insulation is 950~1050℃; b34) The holding time of the second heating and holding period is 0.5~1.5 h; b35) The temperature after the third heating and insulation is 1150~1250℃; b36) The insulation time for the third heating and insulation is 0.5~1.5h; b37) After the third heating and holding, the temperature is lowered to clean the surface of the CVD diamond seed crystal.

Citation Information

Patent Citations

  • Method for preventing seed crystal drifting in MPCVD diamond growth process, and growth method

    CN110565164A

  • High-temperature binding agent of aluminum phosphosilicate and preparation method of high-temperature binding agent

    CN113355025A

Cited By

  • Preparation method of self-supporting substrate for uniform growth of diamond

    CN121556131A

  • A method for the preparation of a self-supporting substrate for the uniform growth of diamond

    CN121556131B